2016
DOI: 10.18203/issn.2454-5929.ijohns20162226
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of conventional versus microdebrider assisted endoscopic sinus surgery in sinonasal polyposis

Abstract: INTRODUCTIONSinonasal polyp refers to edematous projections of nasal mucosa extending through nasal cavity and paranasal sinuses. Prevalence is 4% in general population. 1 Functional endoscopic sinus surgery, conventional or with powered instruments is standard surgical modality in sinonasal polyposis refractive to medical therapy. Microdebriders are the most commonly used powered instruments in endoscopic sinus surgery and continues to evolve in rhinologic surgery. 2 The aim of study was to evaluate the utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…But they used the VAS for nasal obstruction and smell affection mainly. (9)(10)(11)(12) We used of SNOT22, it includes 22 items involving nasal, aural, sleep problems, physical and social performance for more accurate evaluation. The follow up schedules varied between the different studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But they used the VAS for nasal obstruction and smell affection mainly. (9)(10)(11)(12) We used of SNOT22, it includes 22 items involving nasal, aural, sleep problems, physical and social performance for more accurate evaluation. The follow up schedules varied between the different studies.…”
Section: Discussionmentioning
confidence: 99%
“…Bellad et al followed their patients at 1, 3, and 6 months (10). Ghera et al's follow-up regimen was 1 week, 3, and 6 months (11). While the follow-up duration adopted by Kaipuzha et al was 6 months postoperative without a definite schedule for the follow-up visits (9).…”
Section: Discussionmentioning
confidence: 99%
“…3 Numerous advantages of microdebriders over traditional techniques have been cited, including reduced operative time, decreased intra-operative and post-operative bleeding, improved visualisation and precision for tissue removal, decreased traumatisation to tissue with mucosal preservation, decreased crusting and synechiae formation, reduced ostial re-occlusion, and overall faster mucosal healing. 4,5 There are no studies done on different sinonasal diseases and comparison of outcome among individual pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…(5) The microdebrider, which utilizes a vacuum rotatory design to precisely target and resect diseased mucosa (6) , has been shown to reduce intraoperative blood loss and surgery duration while promoting faster postoperative healing. (7) Early in-vitro studies advocated for the safety of microdebrider use in FESS, especially around delicate structures located in the paranasal sinuses. (8) However, this concept has been challenged as evidenced by numerous case studies that have shown that, when misplaced, the indiscriminate aspirating function and limited tactile feedback of the microdebrider can lead to major surgical complications.…”
Section: Introductionmentioning
confidence: 99%